Analisis Keengganan Masyarakat Muslim Desa Mintomulyo Kecamatan Juwana Kabupaten Pati Melaksanaan Zakat Maal (UIN Sunan Kudus, 2018)
The purpose of this study was to explain the causes of the reluctance of the Mintomulyo Village of Juwana District Pati District to carry out zakat maal, to explain the factors that support the Mintomulyo Village community in Juwana District Pati, reluctant to implement zakat maal and to explain the efforts of religious leaders to change the understanding of Mintomulyo Village Juwana District Starch on zakat maal.The results of this study are: First, the Muslim community in the village of Mintomulyo, Juwana Subdistrict, Pati Regency has already carried out zakat maal. But in this study, the reason for the Muslim community who are reluctant to carry out zakat due to the lack of public awareness. Secondly, the factors that support the Muslim community's involvement in Mintomulyo Village, Juwana Subdistrict, Pati Regency, carry out zakat maal. There are two factors, namely the low level of understanding of the community towards zakat maal and unwilling to take part in the recitation. The second factor was the external factor which consisted of the absence of socialization from religious leaders about zakat maal and the absence of village level Zakat Collector Unit (UPZ). Third, the efforts of religious leaders changed the understanding of the Mintomulyo village in Juwana District Pati to the obligations of zakat maal, there are several efforts that can be made to increase the understanding of Muslim society towards zakat maal, namely by fostering through the institution of the Assembly Lecture, by fostering or socializing through the themes of Friday sermons and public holidays.